Healing effects of natural latex serum 1% from Hevea brasiliensis in an experimental skin abrasion wound model, - Marcel Nani Leite; Saulo Nani Leite; Guilherme Ferreira Caetano; Thiago Antônio Moretti de Andrade; Márcio Fronza; Marco Andrey Cipriani Frade (Sociedade Brasileira de Dermatologia, 2020)
Abstract Background Dermabrasion is related with mechanical and surgical traumas on the skin; usually topical antiseptics and/or saline have been used for healing. Natural products for wound healing can also be used for abrasions, such as latex from Hevea brasiliensis. Objective This study aimed to evaluate the in vitro viability and migratory/proliferative effects of latex serum from H. brasiliensis and to compare with a commercially available standard antiseptic solution and saline in experimental dermabrasion on rats. Methods For in vitro evaluation, MTT and scratch assays were used. In vivo testing was performed in 72 rats submitted to dermabrasion, treated with saline, antiseptic, or latex serum. This study evaluated re-epithelialization, neutrophilic infiltration, and the quantification of crust and epidermis. Results Latex showed viability at 1% and 0.1% concentrations and migratory/proliferative activity at 0.01% concentrations. The re-epithelialization was highest in latex group on 7th day. The latex group displayed lower thickness of crusts and greater extent of epidermal layers. The latex and antiseptic groups showed increases of myeloperoxidase levels on the 2nd day and showed important reductions from the 7th day. Study limitations Acute superficial wound model in rats and non-use of gel-cream (medium) without latex. Conclusion In conclusion, non-toxic latex stimulated migration/proliferation of keratinocytes in vitro and significantly accelerated wound healing in animal excoriation models compared to chlorhexidine or saline.